Analysis of the Utilization of Health Services by BPJS Health Participants at Tanjung Public Health Center, Sungai Penuh City - Aditya Pradana; Rapael Ginting; Hartono; Liani Setyarsih (Poltekkes Kemenkes Jambi, 2026)
Background: The implementation of BPJS Health services is not free from challenges and issues encountered in healthcare facilities, such as long waiting times, complicated administrative procedures, and network constraints during P-Care data entry. This study aims to analyze the utilization of health services by BPJS Health participants at Tanjung Public Health Center in Sungai Penuh City. Methods: This study employed a descriptive qualitative method with a case study approach involving 3 health center staff and 10 BPJS user respondents selected through purposive sampling. Data were collected through observation, interviews, and questionnaires. Results: The results showed that 100% of staff identified “slow performance” as the main barrier of the BPJS application, although 66.6% considered the application “easy to use” and 100% reported being “satisfied/very satisfied,” with the main need being a Patient History Check feature. Among respondents, of whom 70% were female and 50% had elementary school education, perceptions of the service were predominantly categorized as “fair,” with service time and complaint handling most frequently rated as “poor.” Conclusion: It can be concluded that the BPJS application is adequate in terms of design but lacks efficiency in performance, while the services at the Public Health Center are perceived as “fair” to “good,” with weaknesses in timeliness and administrative processes. Keywords: Health service utilization, BPJS Health, Public Health Center